1999
DOI: 10.1002/(sici)1521-4109(199905)11:6<406::aid-elan406>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Disposable Amperometric NH Biosensor Based on a Chemically Modified Screen-Printed Carbon Electrode Coated with Glutamate Dehydrogenase, 2-Oxoglutarate, and NADH

Abstract: A screen-printed carbon electrode (SPCE), impregnated with the electrocatalyst Meldola's Blue (MB), has been investigated as the base transducer in a disposable amperometric NH 4 biosensor. The MB-SPCE detects the cofactor NADH when it is polarized at a potential of only 0.05 V (vs. AgaAgCl); electrocatalytic oxidation of the cofactor readily occurs at this potential. The device was converted into an NH 4 biosensor by coating the surface of the MB-SPCE with glutamate dehydrogenase, 2-oxoglutarate and NADH. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…In addition, mass production using screen-printing technology allows fabrication at low cost; the biosensors could therefore be used once and discarded without the inherent problems of contamination. The prototype amperometric biosensor [16] was based on the following enzymatic reaction [17] where GLDH represents glutamate dehydrogenase. The measurement of NH 4 + was again dependent on the detection of NADH by its electrocatalytic oxidation at the MB-SPCE.…”
Section: Ammoniamentioning
confidence: 99%
“…In addition, mass production using screen-printing technology allows fabrication at low cost; the biosensors could therefore be used once and discarded without the inherent problems of contamination. The prototype amperometric biosensor [16] was based on the following enzymatic reaction [17] where GLDH represents glutamate dehydrogenase. The measurement of NH 4 + was again dependent on the detection of NADH by its electrocatalytic oxidation at the MB-SPCE.…”
Section: Ammoniamentioning
confidence: 99%
“…In a previous study (Hart et al 1999), we reported on the development of a prototype amperometric biosensor for the measurement of NH 4 þ in river water at concentrations in the ppb range. In that study, the biosensor was used in conjunction with a standard laboratory-based potentiostat (Hart et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the biosensor was used in conjunction with a standard laboratory-based potentiostat (Hart et al 1999). Although the device could be used to monitor levels in river water at the ppb level, this would not be appropriate for the higher levels present in sewage effluent i.e., above the K m ; therefore, the purpose of the present investigation was to further develop this system for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…An usual procedure for sensor calibration consists in correlating a single point i t of the chronoamperogram with sample substrate concentration [10,14]. Nevertheless, the use of the overall chronoamperometric data is an alternative to improve the reliability of the assay.…”
Section: Introductionmentioning
confidence: 99%